2012
DOI: 10.1524/ract.2013.1990
|View full text |Cite
|
Sign up to set email alerts
|

Separation of oxidized americium from lanthanides by use of pillared metal(IV) phosphate-phosphonate hybrid materials

Abstract: Closing the nuclear fuel cycle in the US poses many challenges, one of which is found in the waste streams, which contain both trivalent lanthanides and actinides. The separation of americium from the raffinate will dramatically reduce the long-term radiotoxicity of the waste. The sorption of americium in both the tri-and pentavalent oxidation states was observed for four M(IV) phosphate-phosphonate ion exchange materials in nitric acid at pH 2. High selectivity was observed for reduced Am(III) with K d values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Previous testing has shown that zirconium and tin(IV) hybrids of ideal composition M(O 3 PC 6 H 6 PO з ) 0.5 (HPO 4 ), with M=Zr and Sn, and sodium titanates were effective in discriminating between ions of low charge ≤2+ and those of 3+ and 4+. 2…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous testing has shown that zirconium and tin(IV) hybrids of ideal composition M(O 3 PC 6 H 6 PO з ) 0.5 (HPO 4 ), with M=Zr and Sn, and sodium titanates were effective in discriminating between ions of low charge ≤2+ and those of 3+ and 4+. 2…”
Section: Approachmentioning
confidence: 99%
“…Recent studies have reported successful separation of americium from lanthanides and curium by oxidation of Am III to Am V or Am VI followed by ion exchange or solvent extraction. [1][2][3] Ionexchange based separation factors are increased as the affinity of the oxidized americium, present as either AmO 2 + or AmO 2 2+ , is diminished compared to that of the triply charged Ln 3+ ions. Our research project seeks to determine if minor actinide separations can be accomplished effectively using inorganic-based materials.…”
Section: Separations 1 Introductionmentioning
confidence: 99%
“…This inadequacy involving the MAs has instigated an effort worldwide to discover a suitable solution. Solvent extraction , has been at the center of this effort, with only a few studies looking into ion exchange. The cost and complexity when incorporating an innovation of this type have proven to be prohibitive when attempting to scale the process . A so-call Group ActiNide EXtraction (GANEX)-type process, , which recovers all the actinides in a single-step technology, would prove to be an advantageous approach to UNF recycle.…”
Section: Introductionmentioning
confidence: 99%
“…Several alternative strategies based on either solvent extraction, ion exchange, ,,, or crystallization have sought to realize this GANEX-type concept by the generation and stabilization of the higher oxidation states of U–Am, through the production of an environment with a high oxidation potential. In the case of Am, this is of utmost importance, which requires a potential of 1.7 V vs NHE to oxidize Am­(III) to Am­(VI), making Am­(VI) the most difficult of the hexavalent transuranic species to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…However, these MPFs remain less explored due to a lack of crystallinity and are designated as unconventional MOFs or unconventional metal-phosphonate frameworks (UMPFs) [ 11 ]. Microporous UMPFs are capable of separating trivalent lanthanides from actinyl at pH ~ 2 binary media [ 12 ]. Single-crystal MPFs have been laboriously prepared and sequester uranyl efficiently from pH ~ 1 solution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%